Students’ Perspectives on ‘Magrib’ As a Skin Color Metaphor in Indonesian Culture: a Linguistic Study - Lakamau, Feronika; Husein, Rahmad (Jurnal Pendidikan Indonesia, 2025)
This research examines the metaphorical use of "Magrib"—a term associated with Islamic prayer time—to describe dark skin in Indonesian culture, exploring its psychological, social, and institutional impacts. Grounded in conceptual metaphor theory (Lakoff & Johnson, 1980) and stigma frameworks (Goffman, 1963), the research employed qualitative methods, including semi-structured interviews and thematic analysis, with 30 dark-skinned university students in North Sumatra. Findings revealed that 36.67% of participants faced discrimination linked to the term, while 30% reported internalized stigma, undermining self-esteem. However, 20% reframed "Magrib" as a symbol of empowerment, demonstrating resilience. Critically, 13.33% highlighted institutional failures to address such bias, underscoring the need for policy reforms. The study situates "Magrib" within global colorism discourses (Hall, 2020) but emphasizes its unique cultural resonance in Indonesia, advocating for educational interventions, diversity training, and inclusive media representation. This research contributes to broader efforts to combat language-based stigma and promote inclusivity in multicultural societies by linking linguistic analysis to systemic inequities.